PENINGKATAN DAYA SAING PRODUK UMKM MELALUI PELATIHAN FOTOGRAFI PRODUK UNTUK STRATEGI MARKETING KREATIF - Muhammad Rijal Alim Rahmat; Anang Setiawan; A. Reski Almaida Dg Macenning (PT. Jurnal Center Indonesia Publisher, 2025)
This community service activity aimed to enhance the competitiveness of SME products through product photography training as part of a creative marketing strategy. The training was conducted during the 63rd Anniversary Education Exhibition of Universitas Negeri Makassar, involving six types of SME products: iced coffee, creative bags, accessories, packaged food, passion fruit drinks, and grilled bread. Participants were equipped with basic photography techniques and hands-on practice. Survey results showed a significant increase in photography skills and participants’ understanding of the importance of visual presentation in digital promotion. The training proved effective in improving SMEs’ promotional capabilities and product appeal in the digital era.